T2 relaxation time measurements are limited in monitoring progression, once advanced cartilage defects at the knee occur: Longitudinal data from the osteoarthritis initiative. Issue 6 (13th September 2013) - Jungmann, Pia M.; Kraus, Mareen S.; Nardo, Lorenzo; Liebl, Hans; Alizai, Hamza; Joseph, Gabby B.; Liu, Felix; Lynch, John; McCulloch, Chuck E.; Nevitt, Michael C.; Link, Thomas M.
Abstract : Purpose: To study the natural evolution of cartilage T2 relaxation times in knees with various extents of morphological cartilage abnormalities, assessed with 3 Tesla MRI from the Osteoarthritis Initiative. Materials and Methods: Right knee MRIs of 245, 45‐ to 60‐year‐old individuals without radiographic osteoarthritis (OA) were included. Cartilage was segmented and T2 maps were generated in five compartments (patella, medial and lateral femoral condyle, medial, and lateral tibia) at baseline and 2‐year follow‐up. We examined the association of T2 values and 2‐year change of T2 values with various Whole‐Organ MR Imaging Scores (WORMS). Statistical analysis was performed with analysis of variance and Students t‐tests. Results: Higher baseline T2 was associated with more severe cartilage defects at baseline and subsequent cartilage loss ( P  < 0.001). However, longitudinal T2 change was inversely associated with both baseline ( P  = 0.038) and follow‐up ( P  = 0.002) severity of cartilage defects. Knees that developed new cartilage defects had smaller increases in T2 than subjects without defects ( P  = 0.045). Individuals with higher baseline T2 showed smaller T2 increases over time ( P  < 0.001). Conclusion: An inverse correlation of longitudinal T2 changes versus baseline T2 values and morphological cartilage abnormalities suggests that once morphological cartilage defects occur, T2 values may be limited for evaluating further cartilage degradation. J. Magn. Reson. Imaging 2013;38:1415–1424. © 2013 Wiley Periodicals, Inc.